Dynamics of neutralizing antibodies against Bovine respiratory syncytial virus in a dairy herd from Santa Fe Province, Argentina - Ferella, Alejandra (2020)
Bovine respiratory syncytial virus (BRSV) is one of the most relevant agents responsible for respiratory disease in cattle from both dairy and beef farms. BRSV is spread by horizontal contact causing a constant presence of seropositive animals that favors viral circulation throughout the year. Moreover, reinfections with BRSV are frequent between animals regardless of their age as BRSV does not confer long-lasting protective immunity. Several studies have demonstrated the circulation of BRSV in cattle from different regions of the world; however, little is known about the dynamics of BRSV infection in cows before and after they begin lactation. The aim of this work was to study the dynamics of BRSV neutralizing antibodies from birth up to 36 months of age in a closed dairy herd of Argentina specifically around the lactation period. Passive maternal antibodies against BRSV started to decrease monthly and became almost undetectable at 8 months of age. We detected two potential infection points at months 11 and 27 after birth, in which 30% and 45% of the animals showed seroconversion, respectively. Specifically, an increase in the proportion of seropositive cows after the start of lactation suggests that they became reinfected around the time they began lactating. We demonstrate the importance of understanding BRSV dynamics in a closed dairy herd to review the vaccination schedule of the animals to achieve protection against BRSV infection.